Achieving high permeability and enhanced selectivity for Angstrom-scale separations using artificial water channel membranes - Yue-xiao Shen (Nature Portfolio, 2018)
Synthetic polymeric membranes used for separations suffer from permeability-selectivity trade-offs. Here the authors demonstrate how a bioinspired pillar[5]arene artificial water channel embedded in a copolymer membrane can improve selectivity while still achieving high permeability.